A rare case of thrombocytosis presentation in patient alcoholic liver disease with portal hypertension gastropathy: a stepwise evaluation - Wiryandari, Ni Putu Nita; Suryana, Ketut (International Journal of Advances in Medicine, 2022)
Thrombocytosis is rarely found in patient with chronic liver disease (CLD). The possibility of reactive thrombocytosis could be due to sustained process such as iron deficiency anemia (IDA) because of occult bleeding. Occult bleeding can happen in CLD patient because of portal hypertension gastropathy (PHG) as complication of portal hypertension. A carefully evaluation of anemia can lead to underlying cause of disease, even in limited of supportive evaluation and some other confounding presentation that is thrombocytosis. We report a case of 54 years-old male patient with severe anemia. He had same symptom previously and got transfusion. Peripheral blood smear showed microcytic hypochromic anemia, anisocytosis, and poikilocytosis even pencil cells (pencil cells or cigar cells) with thrombocytosis. No symptom of acute inflammation setting and no clear blood loss was founded. As patient admitted to smoking and heavy alcohol consumption in the past, Ultrasound was performed for screening of underlying disease that cause occult bleeding. Ultrasound of the liver showed generally increased echogenicity suggestive of liver cirrhosis, splenomegaly and minimal ascites. Thus, our patient clinically be suggestive of CLD with portal hypertension that cause PHG.